Effect of blogging on essay writing performance of Iranian graduate students - Kashani, Hajar (2014)
The purpose of this study was to determine the effect of blogging on the essay writing performance of Iranian graduate students. The writing performance was measured in terms of content, organization, language use, vocabulary, and mechanics. A quantitative experimental design was used to assess the effect of blogging on the Iranian graduate students’ essay writing performance compared to the control group who did not receive the treatment (blogging) and used conventional pen-and-paper tool for essay writing. Sixty four participants were randomly assigned into two groups of pen-and-paper and blogging by using the table of random assignment. The instrument to assess the participants’ writing performance in their pre and posttest was the TOEFL writing test. The instruments were validated by two experienced English language experts before using in this study. Data were analyzed descriptively and inferentially using paired-sample t-test and independent-sample t-test. Results of the pretest and posttest of each group showed that both groups improved in their overall writing performance from pretest to posttest. The pen-and-paper group pretest overall mean was 51.15 while in the posttest overall it increased to 63.11 (p< 0.05). Therefore, there was a significant difference between the pretest and posttest overall mean scores of the pen-and-paper group. The blogging group pretest overall mean score was 49.93 while it increased to 65.48 in their posttest overall mean score (p< 0.05). Thus, there was a significant difference between the pretest and posttest overall mean scores of the blogging group. Posttest results which compared both groups revealed that only in terms of content the blogging group outperformed the pen-and-paper group. It means that in other writing categories such as organization, vocabulary, language use, mechanics, and also in overall writing performance there was no significant difference between two groups after participating in the study. The posttest mean score of pen-and-paper group was 63.11 while for the blogging group 65.4 (p> 0.05) showed there was no significant difference in posttest scores of writing overall performance between pen-and-paper and blogging groups. The post content mean score of pen-and-paper group was 18.37 while the blogging group’s post content mean score was 19.90 (p< 0.05). This showed that there was a significant difference in post content mean scores between pen-and-paper and blogging groups. Results of the study showed that essay writing can enhance the university students’ writing performance by using both conventional and technology-based tools. The study also suggests using blogging as a communicative tool of writing to the ESL/EFL teachers in order to lower the students’ anxiety level compared to the pen-and-paper tool and increase their motivation in writing.